DETERMINANTS OF ZAKAT COMPLIANCE BEHAVIOR IN URBAN MUSLIM ENTREPRENEURS IN MATARAM CITY WEST NUSA TENGGARA - Dahlia Bonang; Tika Widiastuti; Hanifiyah Yuliatul Hijriah; Shafinar Ismail (Akademika : Jurnal Pemikiran Islam, 2023)
This research attempted to explore the determinants of small and medium enterprises (SMEs) compliance behavior in paying zakat (alms). This study involved business owners (SMEs) in the city of Mataram as the population and 176 people as the sample. The data were collected through online survey instruments employing the purposive sampling method. The testing technique and data analysis utilized Structural Equation Modeling (SEM). Hence, the findings discovered that zakat literacy, Islamic egalitarianism, and moral norms influence the intention of SMEs owners to pay zakat. On the other hand, intention affects the owner's choice and compliance to pay zakat. This study is essential for zakat institutions to have a new strategy to encourage SMEs owners to pay zakat, considering the great potential in Indonesia. Distribution of zakat funds to asnaf (noun group of people worthy of receiving a Muslim tithe) fairly and equitably will attract more owners to pay their zakat through zakat institutions. Transparency and fairness in the distribution of zakat funds can increase the level of trust of SMEs owners in zakat institutions.